2016
DOI: 10.3126/jnps.v35i3.13328
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of Mechanically Ventilated Neonates in a Tertiary Level Hospital

Abstract: Introduction: Many sick neonates admitted to neonatal intensive care unit (NICU) require mechanical ventilation but it is associated with various complications and the outcome of neonates is unpredictable. This study aims to identify the indications for mechanical ventilation, complications, co-morbid conditions and outcome of those neonates in terms of survival. Materials and Methods:Retrospective observational study of all neonates who underwent mechanical ventilation from 1 January 2014 to 31 December 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
3
7
1
Order By: Relevance
“…In this study, the total number of cases needed ventilation was (39.8%) and this result is in agreement with this study [7] who reported that ventilated cases were (32%). In this study, the survival rate of mechanical ventilated cases was (23%) while the mortality rate was (77%) and this result is in agreement with this study [7] who showed that survivors were (33.3%) and non survivors were (66.7%) but in contrary with these study [8],[9] , [10] , [11] who reported that the mortality rate was less than that reported in this study and reported to be between 43-67 %.This result may be explained by that the majority of the cases needed MV were preterm and they represented about two thirds of the cases died and in some of these studies MV used were more advanced with more modalities and more efficacy also in some studies reported using HFOV in cases as MAS or in air leak cases as pneumothorax. Sepsis also found to be one of the major complications in this study and one of the major indications for ventilation increasing risk for mortality unlike some of these studies who reported less incidence of sepsis than in this study.…”
Section: Results: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the total number of cases needed ventilation was (39.8%) and this result is in agreement with this study [7] who reported that ventilated cases were (32%). In this study, the survival rate of mechanical ventilated cases was (23%) while the mortality rate was (77%) and this result is in agreement with this study [7] who showed that survivors were (33.3%) and non survivors were (66.7%) but in contrary with these study [8],[9] , [10] , [11] who reported that the mortality rate was less than that reported in this study and reported to be between 43-67 %.This result may be explained by that the majority of the cases needed MV were preterm and they represented about two thirds of the cases died and in some of these studies MV used were more advanced with more modalities and more efficacy also in some studies reported using HFOV in cases as MAS or in air leak cases as pneumothorax. Sepsis also found to be one of the major complications in this study and one of the major indications for ventilation increasing risk for mortality unlike some of these studies who reported less incidence of sepsis than in this study.…”
Section: Results: Discussionsupporting
confidence: 93%
“…This result is in agreement with this study [12] who found that neonates who are between (>34 -< 37) weeks gestational age had the highest survival rate followed by neonates who are between (30 -<34) weeks gestational age who had less survival rate than the previous group followed by neonates who are between (27-<30) weeks gestational age who had the least survival rate. Regarding to the duration of ventilation assistance significant difference (p=0.024) was found between survived group and group who died and this result is in agreement with this study [10] who found that (70.37%) of the cases survived needed (1-7) days of ventilation , also in agreement with this study [8] who found that (75.8%) of the cases survived required ventilation for (4)(5)(6)(7) days .This result may be explained by the fact that short period of MV will cause an inflammation cascade in the lungs as showed in this study [13] and this suggests that weaning from MV should be done as soon as possible, in order to prevent pulmonary sequelae and adverse neurodevelopmental outcomes [14]. In this study, survival rate for RDS was (48.3%)and this is in agreement with both studies [7] and [9] While the mortality rate of RDS was the highest compared to other indications of MV and this result is contrary with this study [10] and with this study [11] who reported that the mortality rate for RDS was only 15-25%.…”
Section: Results: Discussionsupporting
confidence: 90%
“…Overall survival in this study was 37.8%, which is comparable to a few reported from other Intensive care units (NICU) within the country where reported survival rates vary between 33.3 % to 50.8%. 1,7,11 Whereas this survival rate is poorer than those reported by different authors where it varied between 55.5 % to 86%. [14][15][16] This is probably because of larger preterm neonates who are more prone to neonatal sepsis, RDS/HMD and various complications related to different systems and unavailability of surfactant.…”
Section: Discussioncontrasting
confidence: 57%
“…Premature rupture of membrane (PROM) more than 18 hours is a proven risk factor for neonatal sepsis. 6,7 Our study also reflects the fact that neonates with history of PROM more than 18 hours had a poor survival rate of only 21.2 % which was statistically significant.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation